Perubahan Kesiapan Masyarakat dalam Menghadapi Bencana Erupsi Gunung Berapi - Siti Hadiyati Nur Hafida (Universitas Negeri Medan, 2019)
Disasters are things that always happen in Indonesia. The number of disasters in Indonesia should be balanced with the level of community preparedness in the face of disasters. The level of community readiness in dealing with disasters can drive the change in the disaster paradigm in society. Communities often only respond to disaster events with rehabilitation and reconstruction efforts, however, these efforts still cannot afford to minimize disaster victims. This study used qualitative analysis by considering five variables of disaster preparedness, specifically: disaster knowledge, disaster policy, disaster preparedness plans, early warning systems and resource mobilization capabilities. This research was conducted using interview. The results showed that the community of Sidorejo Village had developed a disaster paradigm towards prevention by utilizing community radio infrastructure. The readiness of the community to deal with disasters followed using community radio infrastructure is able to encourage the people of Sidorejo Village to be better prepared and not easily panic during a disaster. Community-based infrastructure will be more effectively used to improve community preparedness because the community manages the infrastructure.